Decreasing consumer animosity: The relationship between fast food businesses and social conflicts in Latin America and the Caribbean - Jose Andres Areiza-Padilla (Cogent Business & Management, 2021)
Consumer animosity represents discomfort towards foreign goods, services and brands originating in countries with which there is some kind of conflict; in this way, a better understanding of consumer behavior in respect of hostilities between countries is sought. On the other hand, the conflicts in Latin America and the Caribbean are often overlooked in the academic literature, which focuses on studying the major Western economies and the great Asian tigers, given their political, economic and military value; for this reason, consumer animosity studies are mostly conducted in these countries. This study seeks to contribute to the scarce literature on consumer animosity in Latin America, through a current conflict between two South American countries, such as Colombia and Venezuela. The data processed through the PLS, allow us to demonstrate how the Colombian consumer, although he may have animosity towards Venezuela, has a positive image of the fast-food restaurants of Venezuelan origin in Colombia. In this way, this study shows that consumer animosity is not widespread, but must be studied specifically for each type of product, service, or brand.
Keywords: 650; consumer animosity; conservatism; national identity; ethnocentrism; image; Latin America